Variability of the total oil content and fatty acid profile of creole avocados from Nuevo Leon, Mexico = Variabilidad del contenido total de aceite y perfil de ácidos grasos de aguacates criollos de Nuevo León, México - Acosta Díaz, Efraín; Álvarez Ojeda, María Genoveva; Guzmán Maldonado, Salvador Horacio; Almeyda León, Isidro Humberto (2019)
Introduction. The State of Nuevo Leon is considered the depositary of a wide genetic diversity of creole avocados (Persea americana var drimyfolia). Objective. The aim of this work was to determine the variability of the total oil content and the fatty acids profile in creole avocados from Nuevo Leon, Mexico. Materials and methods. During the spring and summer of 2016, 36 varieties of creole avocados were collected in the northern and southern region of the State of Nuevo Leon, Mexico for chemical characterization. The commercial variety "Hass" was included as a control. To determine the variability that exists in the content of total oils and fatty acids in the collected materials, analyzes of the main components and conglomerates were carried out. Results. Six fatty acids were detected in the total oil of the creole avocados: palmitic, stearic, oleic, palmitoleic, linoleic and linolenic. The outstanding varieties were "Platano temprano", "Platano delgado", "Huevo de toro", "Cuerno", "Pato", and "Especial", which presented an average of 17.28, 24.93 and 66.29 % more in the content of oleic, linoleic and linolenic acids respectively, and an average of 28.12 % less stearic acid compared to the commercial variety "Hass". According to the analysis of main components, materials with high oleic acid content usually have low palmitic and palmitoleic acid contents. The dendrogram presented six groups within the evaluated materials, most of the outstanding materials are located in groups one and four. Conclusion. High variability in the content of total oils and fatty acids was determined in creole avocados from Nuevo Leon. Therefore, they are considered promising for their incorporation into genetic improvement programs.
Introducción. El Estado de Nuevo León se considera depositario de una amplia diversidad genética de aguacates criollos (Persea americana var drimyfolia). Objetivo. El objetivo de este trabajo fue determinar la variabilidad del contenido total de aceite y el perfil de los ácidos grasos en los aguacates criollos de Nuevo León, México. Materiales y métodos. Durante la primavera y el verano de 2016, se recolectaron 36 variedades de aguacates criollos en la región norte y sur del Estado de Nuevo León, México para su caracterización química. La variedad comercial "Hass" fue incluida como control. Para determinar la variabilidad que existe en el contenido de aceites totales y de ácidos grasos en los materiales recolectados, se realizaron análisis de componentes principales y de conglomerados. Resultados.Se detectaron seis ácidos grasos en el aceite total de las variedades de aguacate criollo: palmítico, esteárico, oleico, palmitoleico, linoleico y linolénico. Las variedades "Plátano temprano", "Plátano delgado", "Huevo de toro", "Cuerno", "Pato" y"Especial", mostraron en promedio 17,28, 24,93 y 66,29 % más en el contenido de ácidos oleico, linoleico y linolénico, respectivamente, y un promedio de 28,12 % menos de ácido esteárico en comparación con la variedad comercial "Hass". De acuerdo al análisis de componentes principales, los materiales con altos contenidos de ácido oleico, por lo general tienen bajos contenidos de los ácidos palmítico y palmitoleico. El dendograma presentó seis grupos con los materiales evaluados, la mayoría de los materiales sobresalientes quedaron ubicados en los grupos uno y cuatro. Conclusión. Se determinó una alta variabilidad en el contenido de aceites totales y ácidos grasos en los aguacates criollos de Nuevo León. Por lo tanto, se consideran promisorios para su incorporación a programas de mejoramiento...
En Revista Agronomía mesoamericana, Volumen 30, número 3 (Septiembre-diciembre 2019)
Descripción basada en el contenido visto el 10 de agosto, 2023
También disponible en formatos EPUB, HTML y XML
Keywords: AGUACATE -- RECURSOS DE GERMOPLASMA -- NUEVO LEÓN (MÉXICO); AGUACATE -- ANÁLISIS QUÍMICO; ACIDOS GRASOS -- COMPOSICION; ACEITES VEGETALES -- EVALUACIÓN